ANALYSIS FACTORS OF AFFECTING TOURISTS VISITING TO JOGER LUWUS, TABANAN BALI - I Made Juniawan, S.Par., M.Par. (Universitas Pendidikan Ganesha, 2023)
The modern shopping souvenirs centers have recently become popular by tourists. The rise of modern shopping centers has slowly replaced the traditional art market, which was a shopping center for tourist that visiting Bali before. With the advantages, this modern shopping centers has almost turn off the traditional art market. The tourist who comes, prefer to choose modern shopping centers than the traditional art markets. Joger is one of the first modern shopping centers for souvenirs, and they still popular especially by domestic tourists. However, than of many modern shopping centers that are easy to reach, near in the city center, or in the tourism areas, the Joger Luwus that located on a rural route and far from the center of the crowd, in fact is always crowded. Therefore, in necessarily have to know the other considerations of consumers in shopping. Mainly related to factors that influence tourist visits to Joger Luwus Bali. This study found that there are seven factors that influence tourist visits. These seven factors have an effect of 71.132 percent on the motivation of domestic tourists in visiting and shopping at Joger Luwus, Bali. This research is considered very important given the lack of scientific publications related to shopping tourism in Bali.